Analysis and comparison of CVS-ADC approaches up to third order for the calculation of core-excited states - Wenzel, Jan; Holzer, Andre; Wormit, Michael; Dreuw, Andreas (The journal of chemical physics, 2015)
The extended second order algebraic-diagrammatic construction (ADC(2)-x) scheme for the polarization operator in combination with core-valence separation (CVS) approximation is well known to be a powerful quantum chemical method for the calculation of core-excited states and the description of X-ray absorption spectra. For the first time, the implementation and results of the third order approach CVS-ADC(3) are reported. Therefore, the CVS approximation has been applied to the ADC(3) working equations and the resulting terms have been implemented efficiently in the adcman program.